OUTCOMES OF MONOPOLAR TRANSURETHRAL RESECTION OF THE PROSTATE FOR BENIGN PROSTATIC HYPERPLASIA AT HA TINH GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of monopolar transurethral resection of the prostate (TURP) in the management of benign prostatic hyperplasia at Ha Tinh General Hospital.Materials and Methods: A retrospective descriptive study was conducted on 60 patients who underwent monopolar TURP for benign prostatic hyperplasia from January 2023 to December 2025 at Ha Tinh General Hospital.Results: The mean age was 76.25 ± 7.9 years. The mean prostate volume was 67.28 ± 27.29 g. The mean operative time was 72.8 ± 29.3 minutes, and the mean irrigation volume was 25.42 ± 10.6 liters. The mean duration of urethral catheterization was 4.55 ± 0.93 days, and the mean hospital stay was 5.28 ± 1.12 days. The IPSS score improved significantly, with the proportion of severe cases decreasing from 78.33% to 1.67%, while mild cases increased to 75%. Quality of life (QoL) improved markedly.Conclusion: Monopolar TURP is a safe and effective method for the treatment of benign prostatic hyperplasia, contributing to significant improvement in patients’ quality of life.
Keywords: Benign prostatic hyperplasia; transurethral resection of the prostate.